唐山工业经济结构调整的战略思考 = Strategies for structural adjustment of TangShan industry - 梁朝群 Liang, Zhaoqun (2010)
在现代经济理论的指导下，本文研究了唐山市，中国产业格局。它强调对工业结构调整对一个城市经济发展的重要性，讨论了目标，原则和产业结构调整政策。特别是，论文探讨了行业的发展，具有战略意义的选择。本论文首先对唐山产业的现状涵盖其长处和短处，讨论。其次是沿着两个方向发展的论点。横向上，横截面数据的沿海城市和重在中国工业城市进行了分析和比较，显示了唐山目前的工业结构的发展阶段。纵向上，从20世纪80年代初至1997年时间序列数据被用来研究在经济发展不平衡的主要原因. Under the guidance of modern economic theory, this dissertation studies the industry structure of Tangshan City, China. It stresses the importance of structural readjustment of industry in the development of an urban economy, discusses goals, principles and policies of industrial structure readjustment. In particular, the dissertation investigates the development and selection of industries with strategic significance. The dissertation begins with a discussion of the present situation of Tangshan industry, covering both its strong and weak points. This is followed by the arguments developed along the two directions. Horizontally, cross-sectional data of coastal cities and heavy industrial cities in China are analyzed and compared to show the development stage of Tangshan's present industrial structure. Vertically, the time series data from the beginning of 1980s through 1997 are used explore the main causes of the imbalance in economic development.